PROGRESS IN NICKEL TARGET DESIGNS FOR DEUTERON IRRADIATION: A MILESTONE IN RADIOISOTOPE PRODUCTION OPTIMIZATION - Usman, Ahmed Rufai; Lawal, Ibrahim Abdullahi (FUDMA JOURNAL OF SCIENCES, 2022)
Medical radioisotopes play significant roles in nuclear medicine, particularly in tumor diagnosis and its therapy. Optimization in production of these important isotopes is very essential for the overall health of the target patients. In this work, we analyzed general trends in the use of various forms of nickel metal as target for radioisotopes production in nuclear accelerators. A careful study of all previously used forms of nickel metal in the literature up to 2016 indicate that different physical forms of the metal, such as its very high purity and impure forms, alloys, compounds and powdered forms have, over the years, been used for various radioisotope productions under deuteron irradiation route, each providing different production effect. The excitation functions of several useful radioisotopes could be studied under deuteron irradiation of nickel. In a recent experimental work by the authors, some very pure, thin nickel foils of natural isotopic composition were also used in form of stacked arrangement for deuteron irradiation. The study found that most of the recent studies on radioisotopes production cross sections use very high purity and solid nickel forms.